Political Culture and Media Genre Beyond the News - Richardson, K.; Parry, K.; Corner, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Exploring the forms and meanings of mediated politics beyond the news cycle, this book encompasses genres drawn from television, radio, the press and the internet, assessing their individual and collective contribution to contemporary political culture through textual analysis and thematic review.
Keywords: Communication; Political science; Cultural policy; Media Studies; Political Science; Media and Communication; Communication Studies; Cultural Policy and Politics